The effects of growth hormone replacement therapy on insulin, lipid profile and calcium in children with growth hormone deficiency - AL-Salami, Rawia M.; AL-Jewari, Majid M.; Abduljabbar, Hanaa A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Growth hormone has multiple effects on the overall form and function of growing body. Aside from these growth stimulating functions, it has marked effects on energy metabolism, it acts on fat cells to reduce the amount of stored fats, promotes protein synthesis in cells and plays a role in regulating the sugar levels in the blood.Objective: to investigate the effect of growth hormone replacement on lipid profile, insulin level, glucose and calcium level in patients with growth hormone deficiency (GHD).Method: A prospective study of 49 children; 37 boys and 12girls with a mean age(13.5±3.3)years attending the Children Welfare Teaching Hospital/ department of endocrinology with short stature proved to have an isolated growth hormone deficiency (other causes of short stature were excluded), with 20 healthy children as control were studied over a period of 11 months( from Oct. 2007 to Aug 2008). . Insulin level ,serum lipid ,blood glucose and serum calcium were estimated for control group and for those with isolated( GHD) prior to and post 11 months of growth hormone replacement therapy(GHRT) .Result: Insulin levels were ( 8.1 µIU/L) in patients with GHD and elevated significantly to( 17.4 µIU/L) after GHRT, without any unfavorable effects on blood glucose. Pre treatment lipid profile values were higher (total cholesterol T-C 4.1 mmol/L ,triglyceride TG 1.5 mmol/L ,low density lipoprotein LDL 2.5 mmol/L, very low density lipoproteins VLDL 0.7mmol/L, than the control group ( T-C 3.9, TG 1, LDL 1.8, VLDL 0.5) . Significant improvement was occurred after treatment (T-C=3.6 , TG=1.2, LDL=1.6 , VLDL=0.5); while pretreatment high density lipoproteins HDL was significantly lower (1 mmol/L) than in control (1.6) which improved significantly post treatment to (1.5) mmol/L. Significant decrement of Post-treatment serum Ca mmol/L (2) noticed as compared to controls (2.3) and to its baseline values (2.2). Significant improvement of height= -3.7 and body mass index BMI =-1.1 Z score to-2.9and 0, 7 respectively were noticed post- treatment. Conclusion: Several metabolic derangements are associated with (GHD) which could be managed effectively with (GHRT).